Corporate governance practice in the context of the political situation in South Africa over the last 25 years. Issue 2 (2nd March 2020) - Kana, Suresh Parbhoo
Abstract : Purpose: This study aims to demonstrate, with reference to developments in the four King Reports on Corporate Governance for South Africa, that institutional culture should be governed with the same rigour applied to other strategic assets to align the pluralistic interests of government, business and society. Design/methodology/approach: Historical narrative and analysis. Findings: Institutional culture should be governed with the same rigour and veracity as more traditional assets to align organisational purpose with political and social interests. Originality/value: This is part of a special issue that looks at the contribution of the King Reports to governance globally.